Process Analytical Technologies and Data Analytics for the Manufacture of Monoclonal Antibodies. Issue 10 (October 2020) - Maruthamuthu, Murali K.; Rudge, Scott R.; Ardekani, Arezoo M.; Ladisch, Michael R.; Verma, Mohit S.
Abstract : Process analytical technology (PAT) for the manufacture of monoclonal antibodies (mAbs) is defined by an integrated set of advanced and automated methods that analyze the compositions and biophysical properties of cell culture fluids, cell-free product streams, and biotherapeutic molecules that are ultimately formulated into concentrated products. In-line or near-line probes and systems are remarkably well developed, although challenges remain in the determination of the absence of viral loads, detecting microbial or mycoplasma contamination, and applying data-driven deep learning to process monitoring and soft sensors. In this review, we address the current status of PAT for both batch and continuous processing steps and discuss its potential impact on facilitating the continuous manufacture of biotherapeutics. Highlights: Process analytical technology (PAT) has evolved from hardware-based analyses for defined biological, biomolecular, and biochemical analytes to a toolbox that encompasses data analytics and soft sensors to monitor and control monoclonal antibody (mAb) manufacture. Engineered cell lines used in batch processes and continuous manufacturing have helped improve qualities and production rates for mAbs. Data analytics has become increasingly important as sensors become smaller, more robust, and increasingly ubiquitous, with soft sensors enabling determination of a rolling baseline of process conditions and consequences during the production of biologics. In-line sensors utilized for downstream processes provide a template for how such sensors might be used as part of PAT in the real-time monitoring of the manufacture of biotherapeutic proteins in both upstream and downstream unit operations.